Quality of electricity in power supply of non-traction consumers of railway transport - Morgunov, Denis N.; Labunsky, Leonid S. (Nexo Revista Científica, 2021)
The article presents the results of the study of the influence of LED lamps with switching power supplies containing power factor correctors on the quality of electricity in the power supply system of non-traction consumers of railway transport. It is noted that the emission of harmonic components of current by electronic loads can cause deviations in the quality of electricity up to the occurrence of emergency situations due to overloads of low (0.4 kV) and medium (6/10 kV) voltage networks. A non-linear electronic load (LED lamp), although equipped with a power factor corrector, causes the generation of a significant level of current harmonics, which significantly affect the operation of the transformer. As a result, the transformer, calculated taking into account the load factor of 0.7 – 0.8, can not be normally operated in the conditions of using electronic load devices. Mathematical modeling of the correction of the modes of the power supply system with nonlinear single-phase loads is performed, provided that the correction devices made on the basis of several condensers and reactors with nonlinear characteristics are used to balance the modes.